Morphology‐ and composition‐controlled silver‐containing rhodium nanoparticles for the oxygen reduction reaction. (13th September 2022) - Hwang, Gyu Seop; Shin, Woojun; Yim, Gyeonghye; Choi, Jae Hyuk; Kim, Young‐Kwan; Jang, Hongje; Kim, Yang‐Rae
Abstract: Rh nanoparticles (RhNPs) have attracted significant attention due to their superior electrocatalytic activity in several energy conversion reactions. However, studies relating their morphology and performance are rare. In this study, three types of RhNPs, i.e., nanoshells, nanoframes, and porous nanoplates, were synthesized via inverse‐directional galvanic replacement. The relationship between the performance of the RhNPs at catalyzing the oxygen reduction reaction (ORR) and their morphology was investigated using cyclic voltammetry, linear sweep voltammetry, the Tafel slope, and electrochemical impedance spectroscopy. X‐ray photoelectron spectroscopy and X‐ray diffraction data revealed that the RhNPs contained different Rh/Ag ratios. All the RhNPs exhibited long‐term stability under acidic conditions. In particular, nanoshell‐structured RhNPs exhibited superior ORR activity as determined from the slope of the Tafel plot, the number of electrons, and the onset potential compared to a commercial Rh electrocatalyst and other RhNPs. Evidently, controlling the morphology and composition of RhNPs greatly facilitates efficient electrocatalysis. Abstract : Three types of rhodium nanoparticles with nanoshells, nanoframes, and porous nanoplates have been prepared via the inverse directional galvanic replacement. These rhodium nanoparticles also have different surface Rh/Ag ratios. Evidently, rhodium nanoparticles with nanoshells show superior activity and long‐term stability for oxygen reduction reaction in acidic solutions.